PENGEMBANGAN MODEL PEMBELAJARAN KEBUDAYAAN DAERAH BERBASIS RISET UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS CALON GURU SD - Dhiniaty Gularso, Beny Dwi Lukitoaji Faiz Noormiyanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2017)
Education curriculum should be prepared to be able to acquaint students with the environment, able to produce graduates who have good moral values and strong character,able to maintain themselves not easily corruption, capable of controlling the nature ofanarchism. The purpose of this study is students can explore the culture based on localwisdom (indigenous wisdom) through research is critical in thinking that led to theexistence of the local culture itself. The method used is research developmentberpendekatan Research and Development which refers Thiaragajan (1994) with the 4Dmodel that define, design, develop and disseminate. Based on the results of this research isthat there is an increase in students' critical thinking skills, can be seen in the graph 9-10meeting showed an average of 82.22, while the average 12-13 meeting showed 82.64. It canbe seen by looking at the improvement of each indicator. It can be concluded that thedevelopment of regional cultural education learning model-based research can improvestudents' critical thinking.Keywords: prospective elementary school teachers, critical thinking skills, learning modelof education research-based regional cultur